Hillary's America [videorecording (DVD)] : the secret history of the Democratic Party - D'Souza, Dinesh, 1961-; D'Souza, Dinesh, 1961-; Schooley, Bruce (D'Souza Media, 2016)
The truth about Hillary Clinton and the history that has been kept secret of the Democratic Party.